Exploring User Satisfaction with Internet Services: A Pilot Test Investigation - Wahyuni, Dian Siti (PT. Lentera Ilmu Publisher, 2024)
This study investigates user satisfaction with Internet services provided by an Internet Service Provider (ISP) using the ITIL V3 framework, with a specific focus on the Service Operation domain. The research evaluates key service operation processes, including Event Management, Incident Management, Request Fulfillment, Problem Management, and Access Management. These processes are analyzed for their maturity levels and effectiveness in meeting user demands. Data collection involved assessing user feedback through targeted questions designed to measure the efficiency and reliability of these service operations. Validity and reliability tests were conducted, confirming that the indicators used in the study are both valid and reliable, with Cronbach’s Alpha values supporting the consistency of the measures. The findings highlight areas of strength and potential improvement for ISPs, offering actionable insights for enhancing service delivery and aligning with ITIL V3 standards to better meet user needs. The study emphasizes the importance of efficient service operations in maintaining high levels of user satisfaction.